Red-cell distribution width and immature to total ratio as predictors of sepsis mortality in preterm neonates - Aziz, Abdul; Hidayah, Dwi; Widiretnani, Septin (Paediatrica Indonesiana, 2025)
Background Preterm neonates are susceptible to various complications and may require invasive procedures that increase the risk of sepsis, which is the third leading cause of mortality in children. Routine laboratory results, such as red-cell distribution width (RDW) and immature to total neutrophil (I/T) ratio, may be useful as predictors of mortality in neonatal sepsis patients. These laboratory markers have undergone limited testing as mortality predictors in preterm neonates with sepsis. Objective To analyze the predictive ability of RDW and I/T ratio on sepsis mortality in preterm neonates. Methods This prospective cohort study included 42 preterm neonates (gestational age 28-36 weeks + 6 days), with birth weight appropriate to gestational age. The diagnosis of sepsis was established based on the high probable sepsis (HPS) and probable sepsis (PRS) criteria scores. RDW and I/T ratio values were obtained at the time of the sepsis diagnosis. Neonatal mortality was defined as death occurring within the first 28 days of life. Receiver operating characteristic (ROC) curve was used to analyze for associations between mortality and the laboratory markers. Results The median RDW in preterm neonates who died was 16.5% (range 14.0-32.7%). This was relatively similar to the median RDW value in preterm neonates who lived (16.25%; range 14.6-34.3%). ROC curve analysis revealed an area under curve (AUC) of 0.541 (95%CI 0.359 to-0.722; P=0.656). The median I/T ratio in preterm neonates who died was 0.13 (range 0.03-0.22), which was similar to the median I/T ratio in preterm neonates who lived (0.15; range 0.11-8.20). The AUC value was 0.387 (95%CI 0.214 to -0.559; P=0.213). Conclusion The RDW and I/T ratio values cannot be used as predictors of sepsis mortality in preterm neonates.